Burnout syndrome in high school teachers in Lima Metropolitana - Delgado Vásquez, Ana (2003)
It was made a study of burnout syndrome in high school teachers of Lima, Perú, considering sex, school classification and year at work. The participants were 764 high school teachers obtained at random considering all school districts (USE) of the city of Lima, Peru. They were teachers of public and private schools. The psychometric analysis shows that the item-test relation is up to norms (>0.20), so reliability was obtained. Also the factor analysis of the items comes up whith one factor explaining the 55.54% of variance, so construct validity was obtained. Also the qualification norms was calculated. The analysis of results points out the comparison considering the levels of burnout and the phases of burnout using. Golembiewski index, between male and female teachers, teachers from public and private schools, and teachers at work.